Przygoda i Wygnanie. Dwie perspektywy doświadczania migracji w mieście, jedno wyzwanie polityki miejskiej - Kubera, Jacek (Człowiek i Społeczeństwo, 2014)
The paper presents two sociological approaches to the migration experience. In the first approach, which corresponds to Georg Simmel’s essay The Philosophy of adventure, migration is regarded as an adventure. In the second approach, which was particularly explored by Abdelmalek Sayad (La double absence), migration is experienced as an exile. However, “adventure” and “exile” describe two different model situations of the migrant’s experience; they both cause the presence of homesickness and the lack of feeling that the inhabited space is a new home. This is why the migrant’s experience of adventure or of exile is treated in the paper as a challenge for every city policy. In the context of contemporary theories (like the metamodernism of Vermeulen and van den Akker), the author of the paper presents the propositions of urban policy which could meet the migrants’ needs and make them real members of the urban community.